Investigations of the barrier perception mechanisms of the blind - PUZYNA, Czesław (Archives of Acoustics, 1979)
Researches carried out in different countries have shown that the capability of recognizing and interpreting the information carried by audible sound waves plays a decisive role in the space orientation of the blind.This article presents the results of: acoustical measurements of test acoustical signals used by the blind such as steps, the tapping of a walking stick and clapping; model investigations analyzing acoustical phenomena occurring in the environment of a conventional barrier such as a screen; open space experiments with a group of blind people in order to define a perception distance for the above barrier under different acoustical conditions; investigations carried out under laboratory conditions defining a relationship between the threshold distance of barrier perception and the area of the barrier surface when using a sonic aid (the so-called sound torch) and without such a device.The results have shown that the threshold distance is proportional to the logarithm of the area of the barrier. Thus for the group of psycho-physical phenomena discussed we may use the Weber-Fechner law where the reaction is measured by the distance of perception and is stimulated by sound waves reflected from the screen surface. The efficiency of perception is influenced by the difference between the acoustical absorption coefficients of the screen and the environment, and also depends on the individual capabilities of the subjects.